Linking Ethics and Economic Growth: a Comment on Hunt - Nicolai J. Foss (Contemporary Economics, 2012)
Hunt (2012) builds on his work concerning ethics and resource-advantage theory to link personal ethical standards, societal norms, and economic growth but offers few details concerning the precise mechanisms that link ethics and growth. This comment suggests a number of such mechanisms - for example, the influence of prevailing ethical norms on the aggregate elasticity of substitution and, therefore, total factor productivity and growth.
Keywords: D40; O40; 330; ethics; trust; competition; productivity; economic growth; resource-advantage theory